2014
DOI: 10.3389/fpsyt.2014.00002
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress in Depressive Patients: HPA Axis Response to GR and MR Agonist

Abstract: Background: Evidence indicates that early life stress (ELS) can induce persistent changes in the hypothalamic-pituitary-adrenal (HPA) axis to respond to stress in the adult life that leads to depression. These appear to be related to the impairment of HPA hormones through binding to glucocorticoid (GR) and mineralocorticoid receptors (MR). The aim of this study was to evaluate the impact of ELS in HPA axis response to challenges with GR and MR agonists in depressed patients.Methods: We included 30 subjects, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 95 publications
1
29
0
17
Order By: Relevance
“…Because prednisolone does not cross the blood brain barrier in relevant amounts when administered in low doses (Karssen et al, 2002) the effect of prednisolone appears to act primarily at the pituitary. A further moderator of MR-function appears to be a history of early live stress, which leads to a reduced awakening cortisol and increased sensitivity for the suppression with prednisolone in comparison to patients without early live stress (Baes et al, 2014). It has been suggested that the history of trauma and these biological characteristics may be related to clinical symptoms of atypical depression (Baes et al, 2014;Juruena et al, 2013;).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Because prednisolone does not cross the blood brain barrier in relevant amounts when administered in low doses (Karssen et al, 2002) the effect of prednisolone appears to act primarily at the pituitary. A further moderator of MR-function appears to be a history of early live stress, which leads to a reduced awakening cortisol and increased sensitivity for the suppression with prednisolone in comparison to patients without early live stress (Baes et al, 2014). It has been suggested that the history of trauma and these biological characteristics may be related to clinical symptoms of atypical depression (Baes et al, 2014;Juruena et al, 2013;).…”
Section: Introductionmentioning
confidence: 96%
“…A further moderator of MR-function appears to be a history of early live stress, which leads to a reduced awakening cortisol and increased sensitivity for the suppression with prednisolone in comparison to patients without early live stress (Baes et al, 2014). It has been suggested that the history of trauma and these biological characteristics may be related to clinical symptoms of atypical depression (Baes et al, 2014;Juruena et al, 2013;). An interesting aspect is that the sensitivity of the MR appears to be a trait rather than a state marker, as acutely depressed and recovered patients are not different (Juruena et al, 2010), which is also reflected in a reduced hippocampal MR expression in depressed patients post mortem independent of depressive state at time of death (Klok et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 Evidências adicionais sugerem que tais pacientes apresentam alterações no eixo hipotálamo-pituitária-adrenal (HPA) indicando assim que a resposta ao estresse está cronicamente ativada. 49,50 No que se refere ao prognóstico deste quadro psicopatológico, pesquisas científicas apontam que quanto mais precoce for realizada as intervenções terapêuticas maiores serão as chances do paciente apresentar um bom prognóstico. 46 A Tabela 1 descreve os critérios diagnósticos para o TEPT.…”
Section: Transtorno Do Apego Reativo E Transtorno De Interação Socialunclassified
“…58,59,60 Diferentes estudos ainda examinam a relação entre o estresse, funcionamento do eixo HPA e depressão no adulto, 61 enfatizando a importância do eixo HPA como um potencial biomarcador para prever a ocorrência e recaída de quadros psicopatológicos no adulto. 49,62 Entretanto deve se considerar que nem todas as pessoas expostas ao EP irão desenvolver psicopatologias, sendo fundamental a compreensão das diferenças individuais na vulnerabilidade e a resiliência aos efeitos patogênicos do estresse. Assim, fatores preexistentes conhecidos para modular a capacidade do organismo de compensar, em resposta ao desafio emocional, poderia interferir em uma adaptação bem sucedida e transmitir a vulnerabilidade no desenvolvimento de tais psicopatologias.…”
Section: Transtornos De Adaptaçãounclassified